1992
DOI: 10.1111/j.1365-2141.1992.tb06439.x
|View full text |Cite
|
Sign up to set email alerts
|

The 32·6 kb Indian δβ‐thalassaemia deletion ends in a 3·4 kb L1 element downstream of the β‐globin gene

Abstract: The Indian delta beta-thalassaemia, with elevated fetal gamma globin gene expression, was previously found to have a large deletion beginning 1 kb 3' of the (A) gamma globin gene at GenBank HUMHBB coordinate 42151, and extending into a new L1 sequence. We have now determined the 3' breakpoint of this deletion, and in doing so we have extended the known beta-globin gene cluster DNA sequence from its end at 73326 to projected GenBank coordinate 79016. These data show that the deletion is 32.6 kb long, terminatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…The 3' regions of two clones (T12 and C8) were not Mouse sequenced. One gene (T12) coded for only nine amino acids and may Chicken be a nonfunctional sequence identity over 208 bp with the human Alu-lA sequence (Gilman et al 1992), 65% identity over 52 bp for the mouse B 1 repetitive element (Shehee et al, 1989), 62% over 110 bp for a rabbit delta-globin pseudogene direct repeat (Margot et al 1989), and 59% identity over 105 bp with the rat B2 repetitive sequence (Matsunaga et al 1990). Two constant region genes coding for 177 amino acids were identified (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3' regions of two clones (T12 and C8) were not Mouse sequenced. One gene (T12) coded for only nine amino acids and may Chicken be a nonfunctional sequence identity over 208 bp with the human Alu-lA sequence (Gilman et al 1992), 65% identity over 52 bp for the mouse B 1 repetitive element (Shehee et al, 1989), 62% over 110 bp for a rabbit delta-globin pseudogene direct repeat (Margot et al 1989), and 59% identity over 105 bp with the rat B2 repetitive sequence (Matsunaga et al 1990). Two constant region genes coding for 177 amino acids were identified (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…7A, B Nucleotide sequences of portions of horse TCRBJ2-C2 intron. A 238 bp of 5' region of intron with closest similarity to human (Gilman et al 1992) and mouse (Shehee et al 1989) repetitive sequences. B 360 bp of 3' region of TCRBJ2-C2 intron including splice acceptor site (underlined) and beginning of TCRBC2 exon 1 (arrow).…”
Section: Resultsmentioning
confidence: 99%
“…L1 elements have repeatedly been implicated in various disease-associated deletions in humans [Henthorn et al, 1990;Gilman et al, 1992;Drechsler and Royer-Pokora, 1996;Segal et al, 1999] although Alu elements seemed to be more frequently found to be involved in non-homologous recombination events than L1 elements. Burwinkel and Kilimann [1998] compiled the breakpoints of 10 non-homologous recombinations involving L1 elements unilaterally and showed that all occurred at different sites of the L1 element.…”
Section: Discussionmentioning
confidence: 98%
“…Many of these deletions represent nonhomologous recombination events that have 5′ breakpoints within the transcriptional units and 3′ breakpoints within or near L1 family repeats. They can be assigned to discrete categories by size, and members of the same category have close breakpoints (Henthorn et al 1986(Henthorn et al , 1990Zhang et al 1988;Feingold and Forget 1989;Gilman et al 1992;Kulozik et al 1992;Motum et al 1992). These structural analyses suggested that the occurrence of the majority of deletions within the β-globin locus was probably related to chromatin configuration (Taramelli et al 1986;Gilman et al 1992), and also revealed a propensity to nonhomologous events mediated by L1 repetitive elements.…”
Section: Introductionmentioning
confidence: 91%